The Students’ Perception on the use of Blue button application in Teaching English for Tourism Course in Indonesia Student Micro Credential Program - Rizqi Claudia Wardani; Selfiani Selfiani (Universitas Pendidikan Muhammadiyah Sorong, 2023)
This study is aimed to describe about students’ perception in the learning process in English for Tourism using Blue Button Application in the Indonesia Student Micro Credential and what are the difficulties that the students faced during learning through the Blue Button Application as the learning media. This research used descriptive Qualitative method that the researcher took the data collection from interview and questionnaire sheets. The subject of this research was the students from English for Tourism class in the Student Micro Credential Program that held by the government collaboration with tourism industry and Universitas Pendidikan Muhammadiyah Sorong. From this research it is found that (1) The students felt easy to use Blue Button Application in learning English for Tourism, (2) the students are easily to access the material like video, text, and picture. (3) students interested with the design of material which presented in the application. (4) the students effectively followed English for Tourism class through Blue Button Application. Meanwhile the difficulties that the students facing during learning English for Tourism using Blue Button Application are (1) the unstable internet connection (2) some students still not familiar with Blue Button Application (3) the upload system that used in the application is very easy for other students to copy. (4) most of the students agreed that they have lack of experience by practicing tourism guide through the application. Keywords: students’ perception, Blue Button Application, English for Tourism